2022
DOI: 10.1186/s12889-022-14321-3
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid of long short-term memory neural network and autoregressive integrated moving average model in forecasting HIV incidence and morality of post-neonatal population in East Asia: global burden of diseases 2000–2019

Abstract: Background To forecast the human immunodeficiency virus (HIV) incidence and mortality of post-neonatal population in East Asia including North Korea, South Korea, Mongolia, Japan and China Mainland and Taiwan province. Methods The data on the incidence and mortality of HIV in post-neonatal population from East Asia were obtained from the Global Burden of Diseases (GBD). The morbidity and mortality of post-neonatal HIV population from GBD 2000 to GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…We reviewed 24 studies(Table 1 ), encompassing a total of 401,389 individuals living with HIV. These studies were conducted in various countries and regions, including 7 from the United States [ 15 , 18 , 19 , 21 , 24 , 25 , 28 ], 10 from China [ 7 11 , 13 , 14 , 16 , 20 , 23 ], and the rest from Spain [ 12 ], Mozambique [ 17 ], Germany [ 22 ], Congo [ 26 ], Uganda [ 27 ], Switzerland [ 29 ], and Canada [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed 24 studies(Table 1 ), encompassing a total of 401,389 individuals living with HIV. These studies were conducted in various countries and regions, including 7 from the United States [ 15 , 18 , 19 , 21 , 24 , 25 , 28 ], 10 from China [ 7 11 , 13 , 14 , 16 , 20 , 23 ], and the rest from Spain [ 12 ], Mozambique [ 17 ], Germany [ 22 ], Congo [ 26 ], Uganda [ 27 ], Switzerland [ 29 ], and Canada [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies comprised 22 cohort studies [ 31 52 ]and 2 nested case-control studies [ 7 – 30 ]. In terms of patient sources, 15 studies originated from multicenter sources [ 31 , 33 – 35 , 37 , 39 , 40 , 42 , 44 48 , 50 , 51 , 53 ], 2 were drawn from a registered database [ 13 , 18 ], and 7 were conducted at single centers [ 8 , 10 , 15 , 20 , 23 , 27 , 30 ]. In a follow-up report, one study specifically focused on in-hospital deaths resulting from the combination of Talaromyces marneffei and HIV infection [ 8 ], while the remaining studies reported deaths during long-term follow-up, with the longest follow-up period extending to 36 years [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation